Clinical Characteristics of Children With COVID-19 in the United Arab Emirates: Cross-sectional Multicenter Study - Farah Ennab; Mariam ElSaban; Eman Khalaf; Hanieh Tabatabaei; Amar Hassan Khamis; Bindu Radha Devi; Kashif Hanif; Hiba Elhassan; Ketharanathan Saravanan; David Cremonesini; Rizwana Popatia; Zainab Malik; et al. (JMIR Publications, 2021)
BackgroundCOVID-19 has infected over 123 million people globally. The first confirmed case in the United Arab Emirates (UAE) was reported on January 29, 2020. According to studies conducted in the early epicenters of the pandemic, COVID-19 has fared mildly in the pediatric population. To date, there is a lack of published data about COVID-19 infection among children in the Arabian region. ObjectiveThis study aims to investigate the clinical characteristics, laboratory findings, treatment, and outcomes of children with COVID-19. MethodsThis cross-sectional, multicenter study included children with confirmed COVID-19 infection admitted to 3 large hospitals in Dubai, UAE, between March 1 and June 15, 2020. Serial COVID-19 polymerase chain reaction (PCR) testing data were collected, and patients' demographics, premorbid clinical characteristics, and inpatient hospital courses were examined. ResultsIn all, 111 children were included in our study and represented 22 nationalities. Of these, 59 (53.2%) were boys. The mean age of the participants was 7 (SD 5.3) years. About 15.3% of children were younger than 1 year. Only 4 (3.6%) of them had pre-existing asthma, all of whom had uneventful courses. At presentation, of the 111 children, 43 (38.7%) were asymptomatic, 68 (61.2%) had mild or moderate symptoms, and none (0%) had severe illness requiring intensive care. Fever (23/111, 20.7%), cough (22/111, 19.8%), and rhinorrhea (17/111, 15.3%) were the most common presenting symptoms, and most reported symptoms resolved by day 5 of hospitalization. Most patients had no abnormality on chest x-ray. The most common laboratory abnormalities on admission included variations in neutrophil count (22/111, 24.7%), aspartate transaminase (18/111, 22.5%), alkaline phosphatase (29/111, 36.7%), and lactate dehydrogenase (31/111, 42.5%). Children were infrequently prescribed targeted medications, with only 4 (3.6%) receiving antibiotics. None of the 52 patients tested for viral coinfections were positive. COVID-19 PCR testing turned negative at a median of 10 days (IQR: 6-14) after the first positive test. Overall, there was no significant difference of time to negative PCR results between symptomatic and asymptomatic children. ConclusionsThis study of COVID-19 presentations and characteristics presents a first look into the burden of COVID-19 infection in the pediatric population in the UAE. We conclude that a large percentage of children experienced no symptoms and that severe COVID-19 disease is uncommon in the UAE. Various laboratory abnormalities were observed despite clinical stability. Ongoing surveillance, contact tracing, and public health measures will be important to contain future outbreaks.